Metaffective fiction: structuring feeling in post-postmodern American literature. Issue 2 (7th February 2019) - Clare, Ralph
ABSTRACT: This essay will suggest that post-postmodern literature does not simply 'return to affect' but that it simultaneously reflects upon the limitations and construction of affect in ways that recall postmodernism's penchant for metafiction and self-conscious textuality. Such writing might fittingly be called 'metaffective fiction.' After a brief summary of Affect Theory as it pertains to contemporary literature, this essay offers as its case study a reading of J.J. Abrams and Doug Dorst's post-postmodern S. against Nabokov's classic postmodern text Pale Fire . My contention is that if metafiction breaks the frame of narrative in order to call attention to its fictive status, metaffective fiction breaks that frame so as to interrogate self-consciously the construction of emotion and affect. Where metafiction underscores the ways in which reality is framed and constructed through narrative, metaffective fiction highlights how emotion and affect themselves are realised and 'framed' or codified. And while metaffective fiction realises that fictionalised emotions aren't real emotions and that affect can never be fully accessible in language, it still both expresses emotion and realises the insufficiencies of that expression. These metaffective fictions attempt to do so as a way of renewing the potential of affect in a neoliberal age that is increasingly commodifying affective labour, leisure, and our everyday emotional lives.